2012
DOI: 10.1590/s0100-879x2012007500076
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the variability of the onset and recovery from neuromuscular blockade with cisatracurium versus rocuronium in elderly patients under total intravenous anesthesia

Abstract: This study was designed to compare the variability of the onset and offset of the effect of two neuromuscular blocking drugs with different elimination pathways in adult and elderly patients during total intravenous anesthesia (TIVA). After Ethics Committee approval and patients' informed consent, the drugs were compared in 40 adult and 40 elderly patients scheduled for elective surgery under TIVA with tracheal intubation who were randomized to receive a single bolus dose of 0.15 mg/kg cisatracurium or 0.9 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…A number of studies have indicated that the prevalance of postoperative residual curarization (PORC) increases with age (2,3).…”
mentioning
confidence: 99%
“…A number of studies have indicated that the prevalance of postoperative residual curarization (PORC) increases with age (2,3).…”
mentioning
confidence: 99%
“…This feature was already demonstrated in the study by Xiaobo et al . [ 9 ]. Comparing rocuronium versus cisatracurium in a prospective randomized trial including 80 patients under total intravenous anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…TOF variability: It was defined by the changes in the TOF responses between the different interval times within the paralysis period and recovery time. This would gauge the stability of the paralysis or decurarization over time [ 9 ]. Tolerance: Hemodynamic tolerance was defined by a significant variation in heart rate above 30% from the baseline value and/or a significant drop of systolic and/or diastolic blood pressures above 30% from the baseline values.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7][8] In our study, there was no significant difference in the onset times and in time taken for the maximum block between the young and the elderly control group. Xiaobo et al 9 concluded that the time of onset was comparable between the elderly and adult patients receiving cisatracurium or rocuronium. This is most likely a reflection of multiple factors.…”
Section: Effect Of Age On Rocuronium Neuromuscular Blockmentioning
confidence: 99%